X-ray image comparison of wind turbine blade waste and eps waste used as aggregates in Portland cement concrete - Marques, Márcio Alexandre [UNESP]; Antunes, Maria Lúcia Pereira [UNESP]; Bini, Marcos Minussi [UNESP]; De Castro, Marcos Vinicius [UNESP] (Trans Tech Publications, 2017)
Transforming industrial wastes into construction materials through recycling is a feasible alternative that contributes to reduce the consumption of natural resources. Besides, modern civil construction seeks strong lightweight building materials. Due to their low density, wind turbine blade manufacturing waste and EPS post-consumer packaging can be used for this purpose. Such work uses X-ray imaging to evaluate the spatial distribution of these wastes in Portland cement concrete. Test specimens were produced containing wind turbine blade waste replacing part of the gravel content, and EPS waste replacing part of the sand content. X-ray images of the test specimens reveal that the waste is distributed homogeneously in the matrix. Furthermore, the mechanical strength of these test specimens meets the requirements of the Brazilian technical standards for non-load bearing concrete blocks.
Keywords: Expanded polystyrene; Incorporation; Portland cement; Wastes; Wind turbine blades; X-ray imaging